2017
DOI: 10.1002/cepa.272
|View full text |Cite
|
Sign up to set email alerts
|

08.51: An experimental study of composite beam‐column joints subject to impact loads

Abstract: Beam-column joints are one of the key elements in steel and composite frames. Till now, many research studies have focused on the behaviour of bare steel beam-column joints and the influence of composite slabs subjected to quasi-static loads. In this study, the research was extended to dynamic loading condition. Two beam-column joint specimens with composite slabs, which were designed based on Eurocode 4, were tested using an MTS drop-weight machine. This loading condition is probably more realistic for joints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(12 reference statements)
0
1
1
Order By: Relevance
“…Unlike previous tests on fin plate connections conducted by the authors [13], complete fracture of the composite joint was not observed in both specimens since they could resist the impact loads. Failure of C75W-M770H3 concentrated in concrete slabs as shown in Figs.…”
Section: Failure Modecontrasting
confidence: 55%
See 1 more Smart Citation
“…Unlike previous tests on fin plate connections conducted by the authors [13], complete fracture of the composite joint was not observed in both specimens since they could resist the impact loads. Failure of C75W-M770H3 concentrated in concrete slabs as shown in Figs.…”
Section: Failure Modecontrasting
confidence: 55%
“…Impact loads were applied to the specimens using an MTS drop-weight testing machine in Protective Engineering Laboratory in Nanyang Technological University [13]. Fig.…”
Section: Experimental Programmementioning
confidence: 99%